Formulation of a Slope Protection Scheme for Senggarang Coastal Embankment Subjected to Tidal Assault - Othman, Irma Errissa Nadia; Chan Chee-Ming; Yahya, Nur Faezah; Sani, Salina; Kean-Hooi, Loke (Journal of Advanced Industrial Technology and Application, 2022)
The seaward slope of embankment that experience erosion due to washing of soil particles from the wave action might resulting the slope become steeper by time and posing a threat to the closest residents. The objective of this research is to examine the existing slope protection methods for Senggarang Coastal Embankment (SCE) in terms of functionality and performance. This paper explores the possible success and failure factors of the slope protection methods by performing the stability analysis of the slope. Desk research were conducted to identify the potential slope protection scheme for SCE then simulated with PLAXIS 2D to refine the proposed solution. Embankment was simulated using silty clay with different water level at 1 m, 2 m and 3 m to see the total displacement, effective stress, excess pore pressure and discharge of seepage. As a result, the deformation for embankment with innovative method is 10% lower than embankment without any slope protection. Meanwhile, the discharge of seepage for embankment with innovative slope protection has reduced by 40% compared to the embankment in the absence of slope protection. In summary, this study has found the water level effect on the displacement and stability of the embankment. The higher the water level, the higher the displacement of the embankment